Prototipe Sistem Monitoring Cuaca dan Peringatan Dini Hujan Berbasis Internet Of Things - Sholichin, Achmad; Susanto, Rudi; Burchim, Nurchim (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
The condition of the air at a certain time and at a certain location over a short period of time is called weather. The term "time" refers to a mixture of meteorological factors that change over time. For example, the weather in the morning may be different from the afternoon and late hours. It is very important for humans to monitor, understand, and prepare for weather events. Weather information can be seen from weather information providers such as BMKG, but weather information on BMKG covers a wide area, so local areas such as villages have different weather even though they are in the same district. In addition, each weather information is presented in three-hour intervals and only covers a wide area, and there are no notifications in each area. Therefore, the purpose of this study is to create a prototype of a real-time weather monitoring system as well as an early warning of rain based on the internet of things (IOT) that can be accessed anywhere and anytime and the results are accurate and in accordance with environmental conditions, where the coverage is local areas such as villages so that there is no difference in weather information and early warning notifications. This research method uses the waterfall method with research stages carried out from data collection, needs analysis, design, creation of tools and program codes, and testing. This research produces weather information such as temperature, humidity, air pressure, wind speed, light conditions, and rain conditions, this research also produces weather notifications that can be used as early warnings of rain. The results of the study were also compared with data from BMKG, namely there was a significant difference between sensor values ​​and notifications. This system can also be an alternative as a tool that can be used for weather monitoring and providing early warning notifications.